Properties of unfired solid bricks produced primarily from thermal power plant fly ash and bottom ash - Trong Phuoc Huynh; Van-Dung Nguyen; Vu-Linh Nguyen; Thi-Thuong Le (CTU Journal of Innovation and Sustainable Development)
In this study, a large amount of fly ash (FA) and bottom ash (BA) from the Nghi Son coal-fired thermal power plant in Thanh Hoa, Vietnam is used in producing unfired solid bricks. FA was utilized to substitute up to 85% (by weight) of the cement amount, while BA was used as a fine aggregate. Test results showed that all bricks produced in this study had a unit weight of 1.51 – 1.68 T/m3 and were classified as Grade M3.5 to M15. As FA replacement level increased, the unit weight, compressive strength, and thermal conductivity of bricks reduced, meanwhile water absorption and water permeability increased. The quality and amount of FA used had a strong effect on the brick’s properties. When the amount of FA used was too much, a part of them did not participate in the chemical reaction but played a role as a fine aggregate.